APPARATUS, METHOD AND COMPUTER PROGRAM FOR MONITORING A SUBJECT DURING A MEDICAL IMAGING PROCEDURE (2020)
The invention refers to an apparatus for monitoring a subject during an imaging procedure, e.g. CT-imaging The apparatus comprises a monitoring image providing unit providing a first monitoring image and a second monitoring image acquired at different support positions, a monitoring position providing unit providing a first monitoring position of a region of interest in the first monitoring image, a support position providing unit providing support position data of the support positions, a position map providing unit providing a position map mapping calibration support positions to calibration monitoring positions, and a region of interest position determination unit determining a position of the region of interest in the second monitoring image based on the first monitoring position, the support position data, and the position map. This allows to determine the position of the region of interest accurately and with low computational effort.